Uber South Africa and digital disruption : innovating for micro-entrepreneurs in an emerging market - Hamann, Ralph, (SAGE Knowledge. Cases., 2017)
In view of a global trend of industry disruption by players in the new sharing economy, this case documents the path of Uber as one such disruptor in the emerging market context of South Africa (SA). It follows various stakeholders in Cape Town, SA, as they experience the opportunities and challenges presented by Uber's transportation model from the time of the company's launch in August 2013, up until a moment of public backlash in April 2016. Watching the actions and reactions of these stakeholders, readers are prompted to consider the meaning and implications of disruption for the different entities and institutions in play.